Effects of caffeine on the inflammatory response induced by a 15-km run competition - Tauler, P.; Martinez, S.; Moreno, C.; Momjo, M.; Martinez, P.; Aguilo, A. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The objective of this study is as follows: 1) to determine the effects of caffeine supplementation on the inflammatory response (IL-6 and IL-10 levels and leukocyte numbers) induced by a 15-km run competition and 2) to examine the effect of caffeine supplementation on the energetic metabolites as well as on the exercise-induced oxidative stress.